Nórmese en el código del trabajo, el despido disciplinario, en garantía de la productividad del empleador - Calva Tapia, Carlos Alberto (2017)
The Constitution of the Republic of Ecuador establishes that the administration of justice, both administrative and judicial, in the performance of their duties and rights guaranteed to the productive system, which depends substantially on the working class in Ecuador, that labor productivity it is a fact that defines both business and workers, who be diminished, it should be taken as a serious offense incurred by the worker, which fits the reasonableness of a criterion linked to a control mechanism by economic activity employers, but not a feature of arbitrariness, thus the disciplinary power of the employer is a discretionary and prudential authority, so the result of a penalty in the dismissal procedure is carried out must be the result of that formal guarantees respect own disciplinary proceedings; disciplinary dismissal, which consists of a maximum penalty when there is a serious and culpable breach of the worker to the legal and contractual standards as the internal labor regulations, and breach of labor obligations, and according to graduation offenses and penalties that the law is established, offenses can make the worker are mild, serious and very serious; so the employer has every right to take decision to terminate the employment relationship; what will be a legal form by the Employer, and it must be built on the principle of causality, ie, it must be prescribed by law as a just cause for termination of employment, not meriting administrative procedure via Seen Well, causal, since this type of procedure is ineffective when substantiated by the fact a serious offense and is part of the discipline of the worker; which will ensure that the procedural subjects, are to the provisions of the Constitution of the Republic of Ecuador, regarding the principles of immediacy and celerity; and the motivation according to the supporting reasons for the dismissal, which in effect when discussing the dismissal implies that justify its exercise, such requirements constitute the causal nature of the dismissal in the sense that the employment relationship can only be dissolved valid unless there is some cause; and the exercise of such disciplinary authority can not be arbitrary, it must be reasonable and observe due process; the worker explaining the content of the facts that motivate the effects of the Disciplinary Despico.